The effect of silver-impregnated catheters on catheter colonization and catheter-related bloodstream infection: a comparison between silver-impregnated and standard catheter - Abu Sa’aleek, Mohammad Ali (International Journal of Research in Medical Sciences, 2017)
The use of antimicrobial central catheter is common in clinical practice to prevent catheter colonization, therefore preventing catheter-related blood stream infection (CRBSI). This paper aims to evaluate evidence from the literature in order to illustrate the effectiveness of one of the most common antimicrobial central catheters, chlorhexidine/silver sulfadiazine central venous catheter, in the prevention of bacterial colonization and CRBSI. Several studies have been selected including randomized control trails (RCTs), meta-analysis and systematic review. The seven RCTs included a total number of 2346 catheters. The patients were either assigned to an intervention group (silver-impregnated central venues catheter) or a control group (standard catheter). These studies were conducted in the USA, Europe, Australia and Brazil from 2004 until 2012. The results revealed that there was a discrepancy in the effectiveness of using silver-impregnated central venous catheter in prevention of catheter colonization and catheter- related bloodstream infection. More recent randomized studies are needed to solve this discrepancy, with a focus on following of infection control measures as the golden standard to prevent colonization and reduction of CRBSI.